PENYIDIKAN TINDAK PIDANA PENGGELAPAN OBJEK FIDUSIA BERDASARKAN UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA DI WILAYAH HUKUM POLRESTA PERKANBARU - Rio Satria Harahap; Erdianto Effendi; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Fiduciary guarantees are material guarantees for movable objects, bothtangible and intangible, in connection with accounts payable between debtors andcreditors. Fiduciary is used for movable and immovable objects. Fiduciary isborn because in practice there are things that are not recommended. So that thereis an action that violates the provisions in the fiduciary guarantee where thedebtor transfers or pawns objects that are still in credit status to another personwithout the knowledge of the first party who is providing the credit facility.This research is a sociological legal research, this research wasconducted at the Pekanbaru Police Office. While the population and sample arethe total number of objects to be studied that have the same characteristics andthe parties used as samples in a study. Sources of data used include primary,secondary, and tertiary materials. Data collection techniques in this study werecarried out by questionnaires, interviews, and literature studies.The results of this study indicate, first, the investigation of the crime ofembezzlement of fiduciary objects based on Law No. 42 of 1999 concerningFiduciary Guarantees in the Pekanbaru Police Legal Area. Second, Obstacles inthe Investigation of the Crime of Embezzlement of Fiduciary Objects Based onLaw Number 42 of 1999 concerning Fiduciary Guarantees in the Legal Territoryof the Pekanbaru Police.Keywords: Investigation, Embezzlement, Fiduciary.